Pengaruh Kompensasi Dan Komunikasi Terhadap Kepuasan kerja Karyawan Pada CV. Sinar Terang Supermarket Kota Probolinggo - Anindia Debira Kumalasahri; Titik Musriati; RR Setyani Hidayati (JUMAD : Journal Management, Accounting, & Digital Business, 2023)
Sinar Terang Supermarket Probolinggo City implements human resources starting from compensating its employees and always communicating with employees to increase the comfort and intimacy of superiors and subordinates. The strategy is implemented for the purpose of providing job satisfaction to its employees. This study aims to determine the effect of compensation and communication partially, bersamaeously, and to determine the dominant variable on employee job satisfaction at CV. Bright Light Supermarket Probolinggo City. This type of research is a type of quantitative research with an associative approach. The population in this study were all employees, totaling 72 employees with a sampling technique that is saturated sample. Source of data used in this research comes from primary data and secondary data. data analysis methods in this study in the form of validity test, reliability test, classical assumption test, multiple regression analysis, coefficient of determination and hypothesis testing. The results of this study indicate the effect of compensation and communication bersamaeously has a significant effect on employee job satisfaction. The results of this study also indicate that compensation partially has a significant effect on employee job satisfaction. And communication partially has a significant effect on employee job satisfaction. The dominant influence in this study is compensation.